Enhancing immune responses of EV71 VP1 DNA vaccine by co-inoculating plasmid IL-12 or GM-CSF expressing vector in mice - Peng, X; Fang, X; Li, J; Kong, L; Li, B; Ding, X (Cellular and Molecular Biology, 2016)
Enterovirus 71 (EV71) is a major causative viral agent for large outbreaks of hand, foot, and mouth disease in children and infants, yet there is no vaccine or effective antiviral treatment for severe EV71 infection. The immunogenicity of EV71 VP1 DNA vaccine and the immunoregulatory activity of interleukin-12 (IL-12) or granulocyte-monocyte colony stimulating factor (GM-CSF) were investigated. DNA vaccine plasmids, pcDNA-VP1, pcDNA-IL-12 and pcDNA-GM-CSF were constructed and inoculated into BALB/c mice with or without pcDNA-IL-12 or pcDNA-GM-CSF by intramuscular injection. Cellular and humoral immune responses were assessed by indirect ELISA, lymphocyte proliferation assays, cytokine release assay and FACS. The VP1 DNA vaccine had good immunogenicity and can induce speciï¬c humoral and cellular immunity in BALB/c mice, while IL-2 or GM-CSF plays an immunoadjuvant role and enhances speciï¬c immune responses. This study provides a frame of reference for the design of DNA vaccines against EV71.